2015
DOI: 10.1007/s12576-015-0418-z
|View full text |Cite
|
Sign up to set email alerts
|

The PI3K/Akt, p38MAPK, and JAK2/STAT3 signaling pathways mediate the protection of SO2 against acute lung injury induced by limb ischemia/reperfusion in rats

Abstract: Sulfur dioxide (SO2) is naturally synthesized by glutamate-oxaloacetate transaminase (GOT) from L-cysteine in mammalian cells. We found that SO2 may have a protective effect on acute lung injury (ALI) induced by limb ischemia/reperfusion (I/R) in rats. The PI3K/Akt, p38MAPK, and JAK2/STAT3 pathways are crucial in cell signaling transduction. The present study aims to verify the role of SO2 on limb I/R-induced ALI, and investigate whether PI3K/Akt, p38MAPK, and JAK2/STAT3 pathways were involved, as well as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 32 publications
2
22
1
Order By: Relevance
“…This work demonstrates that PD-1 up-regulation is also profibrotic through its capacity to enhance STAT3 expression, leading to production of profibrotic cytokines, such as TGF-β and IL-17A. STATTIC inhibition of STAT3 has been shown to reduce collagen-1 content and connective tissue growth factor using the bleomycin murine model of pulmonary fibrosis (3941). Furthermore, it has been previously demonstrated that genetic enhancement and ablation of STAT3 in the murine bleomycin model increase and reduce lung fibrosis, respectively (42).…”
Section: Discussionmentioning
confidence: 80%
“…This work demonstrates that PD-1 up-regulation is also profibrotic through its capacity to enhance STAT3 expression, leading to production of profibrotic cytokines, such as TGF-β and IL-17A. STATTIC inhibition of STAT3 has been shown to reduce collagen-1 content and connective tissue growth factor using the bleomycin murine model of pulmonary fibrosis (3941). Furthermore, it has been previously demonstrated that genetic enhancement and ablation of STAT3 in the murine bleomycin model increase and reduce lung fibrosis, respectively (42).…”
Section: Discussionmentioning
confidence: 80%
“…Limb I/R-induced ALI animal models were performed the same as previously described in detail [7, 11]. The SD rats were anesthetized via ip administration of sodium pentobarbital (40 mg/kg body weight).…”
Section: Methodsmentioning
confidence: 99%
“…The phosphatidylinositol 3'-kinase (PI3K)/Akt pathway, Janus kinase 2/signal transducer and activator of transcription 3 (JAK/STAT3) pathway, and p38 mitogenactivated protein kinase (MAPK) pathway play pivotal roles in cell signal transduction, inflammation, stress, apoptosis, cell cycle, and cell growth (26). Akt is a serine/threonine kinase that acts downstream of PI3K.…”
Section: Signal Transduction Pathwaysmentioning
confidence: 99%
“…Akt is a serine/threonine kinase that acts downstream of PI3K. Akt has a variety of functions in apoptosis, proliferation, and differentiation (26). Akt and MAPK activate redox-sensitive transcription factor NF-E2-related factor 2 (NrF2), which is essential for protection against oxidative stress in different forms of ALI.…”
Section: Signal Transduction Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation